Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1590/s0102-86502007000600010
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative embolization of the splenic artery in patients that underwent splenectomy for immune thrombocytopenic purpura

Abstract: Transfusion of platelets, red blood cells, or both is usually necessary immediately after splenic artery ligature in patients with immune thrombocytopenic purpura who undergo splenectomy. Purpose: To investigate whether preoperative embolization of the splenic artery reduced the need for transfusion of platelets, red blood cells, or both. Methods: Twentyseven consecutive patients that underwent splenectomy for purpura between October 1999 and March 2006 performed by the same surgical team were enrolled. The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 4 publications
2
12
0
Order By: Relevance
“…The value of preoperative SAE observed in our study for a better control of intraoperative blood loss during splenectomy confirms the results of previously published studies in the management of patients with hypersplenism [ 10 , 11 ], as there was no need for blood transfusion in the SAE patient group. In 2007, Bau et al [ 10 ] reported on a patient series without preoperative SAE. They had severe haemorrhagic complications that required transfusions of platelets in 65% of cases and of red blood cells in 47%, while there was no need for blood transfusion in their preoperative SAE group.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The value of preoperative SAE observed in our study for a better control of intraoperative blood loss during splenectomy confirms the results of previously published studies in the management of patients with hypersplenism [ 10 , 11 ], as there was no need for blood transfusion in the SAE patient group. In 2007, Bau et al [ 10 ] reported on a patient series without preoperative SAE. They had severe haemorrhagic complications that required transfusions of platelets in 65% of cases and of red blood cells in 47%, while there was no need for blood transfusion in their preoperative SAE group.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, there was an overall improvement in the platelet count after embolisation in the SAE patient group (mean 380,000 U/ μL, on day 10 post surgery). This finding provides a better evidence on the effect of the SAE and confirms other many older series [ 5 , 10 , 11 , 21 ]. SAE leads to a softer and smaller spleen, improves the surgical view and reduces the incidence of bleeding [ 11 , 22 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The splenic artery ligation in early splenectomy allows the output of blood by the spleen splenic vein and reduces the size of the spleen due to the inflow of splenic blood into the portal circulation [22][23][24][25] . According to the literature during the removal of larger spleens there is inflow of more than 500 ml of whole blood 1 .…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…Preoperative splenic artery embolization has been suggested as a potential way to reduce this complication [7]. Embolization can decrease the need for transfusion in patients with immune thrombocytopenic purpura when performed prior to splenectomy [8]. Contrast-induced nephropathy is a potential adverse outcome of the embolization procedure, particularly in patients with such risk factors as chronic renal disease, diabetes mellitus, advancing age, congestive heart failure, hypotension, and shock.…”
Section: Discussionmentioning
confidence: 99%